Anne of the Island - Montogomery, L. M. (New York Bantam Books, 1998)
Focuses on Anne Blythe as a mother of six, managing a busy household in19th-century Prince Edward Island.
English
Keywords: Motherhood and Family Life; Childhood Adventures and Misadventures; Marriage and Romance; Home and Community